Unusual sequela of neck trauma: External carotid pseudoaneurysm and jugular fistula - Kenza Berrada; Ibtissam El Ouali; Abdelkader Squali; Meryem Fikri; Mohamed Jiddane; Firdaous Touarsa (Radiology Case Reports, 2025)
Carotid-jugular fistulas (CJFs) are rare vascular anomalies that typically arise after trauma or iatrogenic injury, such as central venous catheterization. In exceptional cases, they may result from the rupture of a pseudoaneurysm into an adjacent vein. We report a unique case of a 42-year-old man who presented with a right-sided pulsatile neck mass ten years after a knife wound. Imaging revealed a pseudoaneurysm of the external carotid artery communicating directly with the internal jugular vein, forming a CJF. This case highlights the importance of long-term vigilance following cervical trauma, as vascular complications such as pseudoaneurysms and arteriovenous fistulas may present years later.